Wind-induced motions of a multi-storey building in serviceability limit state - Sigurjón Gauti Sigurjónsson 1994- (2021)
In this preliminary study, comfort condition of a medium-rise building due to wind induced vibration is assessed according to three international design codes, that is: EN 1991-1-4, AIJ recommendations and AS/NZS 1170.2. A conceptual concrete reinforced building located in the capital area of Iceland is considered. The building has 22 storeys, height of 80 m and width and depth of 36 m and 18 m respectively. Various parameters determine the dynamic response of the building in terms of peak acceleration such as number of storeys, side ratio of a building, stiffness and mass distribution, damping ratio, as well as parameters that control the wind intensity and characteristic. The along-wind acceleration response is evaluated according to all three code-based approaches but only the AIJ recommendations and AS/NZS 1170.2 provide methods to evaluate the across-wind response. EN 1991-1-4 gives the largest estimated along-wind response for fixed damping ratio when wind acts on either side of the building. Some discrepancy is observed between the codes for the across-wind response when wind acts normal to the long-side of the building. It is determined that the across-wind response of the building is higher than the along-wind response for wind that acts normal to the short-side of the building and exceed the human comfort limits proposed by ISO 10137 and the AIJ guidelines for terrain category II as defined in EN 1991-4. Þessi ritgerð fjallar um frumathugun á vindsvörun á íslensku háhýsi þar sem hröðun byggingarinnar er áætluð samkvæmt þremur alþjóðlegum hönnunarstöðlum, þ.e. EN 1991-1-4, AIJ og AS/NZS 1170.2. Áætluð hágildi hröðunar eru síðan borin saman við tvær mismunandi þægindakröfur sem gefnar eru í ISO 10137 og AIJ og miðast við notmarkaástand. Byggingin sem er rannsökuð er huglæg eða sviðsett og gert ráð fyrir því að hún sé staðsett á höfuðborgarsvæðinu. Hún er 80 m há með rétthyrndan grunnflöt 36 m x 18 m. Ýmsir stikar hafa áhrif á vindsvörun bygginga svo sem hæð, hlutfall á milli hliða, stífni og ...